2016
DOI: 10.1530/erc-16-0130
|View full text |Cite
|
Sign up to set email alerts
|

Is there an effect of ghrelin/ghrelin analogs on cancer? A systematic review

Abstract: Ghrelin is a hormone with multiple physiologic functions, including promotion of growth hormone release, stimulation of appetite and regulation of energy homeostasis. Treatment with ghrelin/ghrelin-receptor agonists is a prospective therapy for disease-related cachexia and malnutrition. In vitro studies have shown high expression of ghrelin in cancer tissue, although its role including its impact in cancer risk and progression has not been established. We performed a systematic literature review to identify pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 132 publications
(251 reference statements)
3
31
0
1
Order By: Relevance
“…Circulating ghrelin levels also increase in the presence of low BMI and malnutrition, and ghrelin levels decrease with increasing BMI and obesity. 31 The NIT study, in particular, was undertaken in a population who could be classified as under nourished using any metric 32,33 which likely explains the higher concentrations of this orexigenic hormone in the NIT cohort (mean ghrelin 1,022 pg/ml controls), relative to Shanghai (mean ghrelin 743 pg/ml controls) or previous studies in Finland (mean ghrelin 802 pg/ml controls) 15 and Iran (median ghrelin 672 pg/ml controls). 25 Future studies investigating the association of ghrelin levels with subsequent incidence of esophageal, and other cancers, are clearly merited.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating ghrelin levels also increase in the presence of low BMI and malnutrition, and ghrelin levels decrease with increasing BMI and obesity. 31 The NIT study, in particular, was undertaken in a population who could be classified as under nourished using any metric 32,33 which likely explains the higher concentrations of this orexigenic hormone in the NIT cohort (mean ghrelin 1,022 pg/ml controls), relative to Shanghai (mean ghrelin 743 pg/ml controls) or previous studies in Finland (mean ghrelin 802 pg/ml controls) 15 and Iran (median ghrelin 672 pg/ml controls). 25 Future studies investigating the association of ghrelin levels with subsequent incidence of esophageal, and other cancers, are clearly merited.…”
Section: Discussionmentioning
confidence: 99%
“…However, ghrelin also has a effects throughout the body. Ghrelin modulates growth hormone secretion (and thus, IGF-1 production), and can have beneficial effects on muscle mass, inflammation, cardiac function, gastric motility, and many others [95]. Ghrelin concentrations are increased in people with CHF but food intake is decreased, suggesting loss of normal feedback and resistance to ghrelin [96][97][98][99].…”
Section: Ghrelinmentioning
confidence: 99%
“…Additionally, clinical studies with anamorelin [58] and ghrelin [59] have also shown no significant effect on overall survival compared with placebo. Long-term, large-scale clinical trials are required to determine whether treatment with ghrelin receptor agonists could stimulate tumour growth [60]. …”
Section: Discussionmentioning
confidence: 99%